Investigations on foliar epidermis in some Rubiaceae - Patil, C R; Patil, D A (Journal of Phytology, 2011)
The paper reports foliar epidermal features of 20 unstudied species belonging 12 genera of the family Rubiaceae. The foliar stomates although paracytic generally in the taxa investigated, other types are also noticed rarely or occasionally on the same surface. The other epidermal features such as stomatal index (S.I) and frequency (S.F), stomatal abnormalities, cell wall contours, cell inclusions, etc. have been described in detail. Significance of various epidermal features in taxonomy of the taxa investigated is discussed.Â